2020
DOI: 10.31744/einstein_journal/2020ao5175
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inducible urticaria: confirmation through challenge tests and response to treatment

Abstract: Objective: To evaluate the positivity of challenge tests of patients suspected of chronic inducible urticaria and the response to treatment. Methods: A retrospective study of electronic medical records of patients suspected of chronic inducible urticaria. All patients were submitted to challenge tests with triggering stimuli, according to the clinical history and, subsequently, the response to drug treatment was evaluated. Results: A total of 191 patients with suspected chronic inducible urticaria were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(53 reference statements)
3
0
0
3
Order By: Relevance
“…The observation that CIndU patients were younger than those with CSU plus CIndU is consistent with the findings of Jankowska‐Konsur et al's study 15 . This contrasted with Pereira et al's study 13 , wherein no significant age difference between groups was identified. Additionally, in accordance with earlier research 16‐18 , our study indicated that CHoU tends to manifest in younger individuals compared to other subtypes of CIndU 16–18 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observation that CIndU patients were younger than those with CSU plus CIndU is consistent with the findings of Jankowska‐Konsur et al's study 15 . This contrasted with Pereira et al's study 13 , wherein no significant age difference between groups was identified. Additionally, in accordance with earlier research 16‐18 , our study indicated that CHoU tends to manifest in younger individuals compared to other subtypes of CIndU 16–18 …”
Section: Discussionsupporting
confidence: 89%
“…In the literature, the rate of CSU plus CIndU is generally mentioned for patient populations in which CSU patients constitute the majority, and the rate ranges from 9% to 36%. 7,12 Similar to ours, Pereira et al 13 reported a 38.2% CSU plus CIndU rate in their CIndU population. However, the rate of patients with more than one CIndU subtype was 21.5%, compared to ~5% in ours.…”
Section: Discussionsupporting
confidence: 86%
“…По данным некоторых авторов, распространённость ХолинергК ниже в тропических странах и имеет продолжительность персистенции симптомов 4,3 года [4]. В отношении продолжительности ХолинергК в других климатических зонах данные литературы ограничены, однако все исследователи описывают многолетнюю длительность заболевания [5]. Наиболее подверженная заболеванию ХолинергК возрастная группа -молодые взрослые: до 20% пациентов болеют в возрасте 26-28 лет [6].…”
Section: обоснованиеunclassified
“…Результаты проведённого исследования демонстрируют превалирование молодой группы (средний возраст участников составил 26,5 лет); для большинства пациентов характерен ранний возраст дебюта симптомов, что коррелирует с мировыми данными [2,6]. Многие авторы отмечают многолетнюю продолжительность заболевания, что также подтверждает данные нашего анализа (длительность в среднем 57,5 месяцев) [4,5]. Выявленная корреляция между ранним возрастом дебюта и бóльшей продолжительностью ХолинергК представляет клинико-практическую значимость, повышая настороженность медицинского сообщества в отношении данной когорты молодых пациентов.…”
Section: обсуждение результатов исследованияunclassified
“…I N P R E S S DOI: https://doi.org/10.36691/RJA1573 Для верификации диагноза ХИНДК используют анамнестические данные, подтверждающие фотографии кожного процесса, результаты провокационного тестирования [26]. Проведение провокационных тестов позволяет определить порог специфического триггера, оценить эффективность лекарственной терапии и дать персонифицированные рекомендации пациенту [27,28].…”
Section: A R T I C L Eunclassified